Hello! In the above problem (from 14.02.2018) for translation of the formula, I have a different solution to the one given in the image above.

Is it accepted answer if I translate with the following steps:

= AXXFGFGF(a ⊕ b)

= AXXGF(a ⊕ b) (because: Alternation of F,G ending with F = GF)

= AGF(a ⊕ b) (because: XXGF = GF)

= AGAF(a ⊕ b)

Note: I came across the rule **XXGF = GF** from the solutions stated in the paper dated **27.08.2021**, an image of which is attached below:

Thanks for your support.!